The relationship between employee empowerment and organizational commitment among non-staff academic in Universiti Teknologi MARA Cawangan Pahang Kampus Jengka / Amira Mohamad Khalid - Mohamad Khalid, Amira (Faculty of Business and Management, 2019)
The final report project was carried out in order to fulfill the requirement of the Academic Project (ASM662). The study was conducted in UiTM Jengka, Pahang. There are three main objectives which are to identify the level of employee empowerment that has been practiced in the organization, to identify the level of commitment among the employee in the organization, and to determine the relationship between employee empowerment and organizational commitment. By referring to the table of Krejcie and Morgan (1970), the population of non academic staff in UiTM Jengka, Pahang was 309 hence the sample sizes taken was 169. The sampling technique used is simple random sampling. From the overall findings, it can be concluded that for employees in UiTM Jengka, there is no relationship between employee empowerment and organizational commitment. Future researchers might examine relationship between employee empowerment and other dependent variables such as job satisfaction and job performance.